Obesity and oxidative stress: potential mechanisms in endometrial disorders - Wang, Yiwei; Chen, Zhilin; Wang, Ruiqing; Song, Aiqun; Zhang, Yangpu (Frontiers in Endocrinology, 2026)
Obesity is a systemic metabolic disorder that is inducing factor for other diseases such as diabetes mellitus, cardiovascular diseases, malignancies, hepatic dysfunction, renal dysfunction and endometrial diseases. Emerging evidence has shown that Oxidative stress (OS) plays a key mediator in the development of obesity and its complications. Obesity itself can produce OS through several different pathways, including disrupting energy metabolism, interfering with endocrine homeostasis, inducing systemic chronic inflammatory responses and changing gut microbiota. Among the complications induced by obesity, endometrial diseases have been closely related to OS. OS damages molecular phenotype of endometrial cells, induces endometrial apoptosis and affects endometrial angiogenesis, decidualization and receptivity. In this review, we will summarize the relationship among obesity, OS and endometrium, that is, how obesity can induce OS with various pathways, how OS damage endometrial structure and function, and further explore the relationship between OS and obesity-associated endometrial disorders and the potential of using antioxidant strategy as a new therapeutic method.